Genome-wide analysis of R2R3-MYB transcription factors in Boehmeria nivea (L.) gaudich revealed potential cadmium tolerance and anthocyanin biosynthesis genes - Feng, Xinkang; Abubakar, Aminu Shehu; Chen, Kunmei; Yu, Chunming; Zhu, Aiguo; Chen, Jikang; Gao, Gang; Wang, Xiaofei; Mou, Pan; Chen, Ping (Frontiers in Genetics, 2023)
A total of 105 BnGR2R3-MYB genes were identified from ramie genome and subsequently grouped into 35 subfamilies according to phylogeny divergence and sequences similarity. Chromosomal localization, gene structure, synteny analy-sis, gene duplication, promoter analysis, molecular characteristics and subcellular localization were accomplished us-ing several bioinformatics tools. Collinearity analysis showed that the segmental and tandem duplication events is the dominant form of the gene family expansion, and duplications prominent in distal telomeric regions. Highest syntenic relationship was obtained between BnGR2R3-MYB genes and that of Apocynum venetum (88). Furthermore, tran-scriptomic data and phylogenetic analysis revealed that BnGMYB60, BnGMYB79/80 and BnGMYB70 might inhibit the biosynthesis of anthocyanins, and UPLC-QTOF-MS data further supported the results. qPCR and phylogenetic analysis revealed that the six genes (BnGMYB9, BnGMYB10, BnGMYB12, BnGMYB28, BnGMYB41, BnGMYB78) were cadmium stress responsive genes. Especially, the expression of BnGMYB10/12/41 in roots, stems and leaves all increased more than 10-fold after cadmium stress, and in addition they may interact with key genes regulating flavonoid biosynthesis. Thus, a potential link between cadmium stress response and flavonoid synthesis was identified through protein inter-action network analysis. The study thus provided significant information into MYB regulatory genes in ramie and may serve as a foundation for genetic enhancement and increased productivity.